CUSTOMER SATISFACTION IN RETAILING OF FMCGs IN THIRUVANANTHAPURAM DISTRICT - Prasasthan M.K. and Dr. JubilyNavaprabha
In this current changing business scenario, retail industry has witnessed major revolution and global attention. Retailing is one of the most rapidly growing and promising industries in Indian Economy. Retailing is an important social institution in Kerala because about 30 per cent of what a customer spends goes on products & services that they buy from retailers. In the midst of stiff and fierce competition and increased number of retail outlets providing a variety of FMCG products, customers have become accustomed to patronizing multiple outlets. Traditionally, retailers have relied only on differentiation of products and services to retain their customers and also to satisfy the consumers. However, times have changed, due to fierce competition from new players entering the market, imitation of new features and increase in number of new offers, customers have acquired new choices and they have also become more price sensitive, which has forced marketers to adapt differentiated and customer oriented strategies in order to enable them to stand out in the competition and gain a competitive edge. Retailers have recognized this trend and are of the view that customer satisfaction plays a role in the success of retailing business. Therefore it has become important for FMCG retail stores to try and manage customer satisfaction. Customer satisfaction occurs when the value and customer service provided through a retailing experience meet or exceed consumer expectations. Customer satisfaction is considered very important now a day, it shows how firms are committed to provide quality product or services to their customers that eventually increase customer loyalty. Retail business units are now busy in finding out new and innovative ways to satisfy their customers so that they will stick on the company. The present study is to assess the level of satisfaction of the customers from the various services of retailing of FMCGs in Thiruvananthapuram district